The effect of protein intake levels on early postoperative outcomes following impacted mandibular third molar removal: a pilot study - Canseda Avağ; Merve Safa Avağ; Özgür Sakarya; Attila Vural (BMC Oral Health)
Abstract Background This study aimed to evaluate the effect of protein intake on early wound healing following the surgical removal of impacted mandibular third molars, and to explore its associations with postoperative outcomes such as trismus, edema, pain, and oral health-related quality of life. Methods Patients with asymptomatic impacted mandibular third molars classified as easy or medium difficulty according to the Pernambuco index were included. Dietary protein intake over the past month was assessed using a food frequency questionnaire and a 24-hour recall. Early wound healing was evaluated using the Early Wound Healing Index (EHI). Trismus was assessed by measuring maximum interincisal opening, swelling through linear facial measurements, and pain using a visual analog scale (VAS). Results Twenty-five patients (16 females, 9 males) aged 19–33 years (mean 23.3 ± 2.88) were analyzed. No significant differences were found between the study groups regarding age, sex, body mass index, surgical difficulty, or operation duration. Patients with high protein intake experienced a significantly greatest decrease in mouth opening on the 3rd postoperative day (p = 0.004). Facial swelling on day 3 was significantly greater in the high protein intake group compared to the low and normal intake groups (p = 0.023), while pain scores on day 1 were significantly lower (p = 0.009). Protein intake was positively associated with EHI scores on day 7, indicating improved early wound healing (p = 0.019), whereas no significant association was observed on day 1 (p = 0.081). No significant relationship was found between protein intake and OHIP-14 scores at any time point (p = 0.211, p = 0.462, and p = 0.704, respectively). Conclusions Higher protein intake was associated with improved early wound healing and modulation of postoperative outcomes, including reduced pain severity and enhanced functional recovery following third molar surgery. These findings underscore the value of nutritional assessment and support as part of postoperative care. Further studies with larger cohorts are warranted to validate these results and clarify the underlying mechanisms.